"You're a teacher you're a mother, you're a worker": Gender inequality during COVID‐19 in Ireland. Issue 4 (10th January 2021) - Clark, Serena; McGrane, Amy; Boyle, Neasa; Joksimovic, Natasha; Burke, Lydia; Rock, Nicole; O' Sullivan, Katriona
Abstract: The novel coronavirus (COVID‐19) was declared a global pandemic in March 2020. Unlike previous highly contagious diseases that brought the threat of global instability this century such as SARS‐CoV, Zika virus (ZIKV), Swine flu (H1N1), and the Avian flu (H5N1), COVID‐19 was unable to be contained. Global restrictions were implemented to curb the spread of the virus, which included but were not limited to the closure of all educational institutions and the advice to engage in remote working. This study aims to understand the experience of working mothers who managed work and home duties during the COVID‐19 pandemic in Ireland. Thirty working mothers were interviewed in this study, and qualitative analyses were conducted to gain insight into their work and family life during the restrictions. The findings of the analysis indicate that working mothers have been negatively impacted by COVID‐19 in relation to their psychological well‐being, experiences of negative emotions, and the redefinition of family dynamics, in which working mothers have adopted additional and disproportionate care burden. These findings are consistent with the current research arguing that COVID‐19 has highlighted an increase in the gender gap in domestic labor as well as the undermining of career advancement for working mothers.